DETERMINASI JUMLAH WAJIB PAJAK, PENAGIHAN PAJAK DAN PEMERIKSAAN PAJAK TERHADAP PENERIMAAN PAJAK PENGHASILAN BADAN - Triana Rofika Putri; Khy'sh Nusri Leapatra Chamalinda (Jurnal Akuntansi, 2024)
Efforts to increase tax revenue continue, but in its implementation often experiences obstacles. The purpose of this study was to determine the effect of the number of taxpayers, tax collection, and tax revenue on corporate income tax revenue at KPP Pratama Bangkalan. The data source is secondary data from KPP Pratama Bangkalan using a ratio scale. The population of this study is all corporate taxpayer tax data, and the sample determination uses purposive sampling method. The sample used is the amount of corporate income tax revenue, the number of registered corporate taxpayers, the number of corporate income tax liabilities and the number of collectible corporate income tax liabilities and the number of SKPKB issued at KPP Pratama Bangkalan on a monthly basis during 2018 - 2022. Data analysis was carried out using IBM SPSS software. The results of this study indicate that the number of taxpayers and tax collection has no effect on corporate income tax revenue, while tax audits have an effect on corporate income tax revenue.  Keywords: Taxpayers, Tax Collection, Tax Audit, Tax Revenue